Charlottetown Living Wage 2020 - Saulnier, Christine (Canadian Centre for Policy Alternatives, Nova Scotia Office, 2020)
The living wage rate for Charlottetown, PEI is $19.30 per hour. This 2020 living wage is calculated to follow the principles and methodology laid out in the Canadian Living Wage Framework. The calculation for Charlottetown follows how the wage has been calculated in our Atlantic Canadian jurisdictions, including the most recent report with wages calculated for various communities in Nova Scotia, as well as Saint John in New Brunswick. In 2019, the living wage was calculated for St. John’s in Newfoundland and Labrador.